2008
DOI: 10.1089/jmf.2007.0155
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperglycemic Effect of Fomitopsis pinicola Extracts in Streptozotocin-Induced Diabetic Rats

Abstract: The antihyperglycemic effect of a water extract (WE) and an alkali extract (AE) of the Fomitopsis pinicola fruit body was studied in streptozotocin (STZ)-induced diabetic rats. The STZ-induced diabetes mellitus (DM) control group lost a significant amount of body weight, whereas the normal control group (NC) gained weight; however, the DM-AE group gained a significant amount of weight, with weight gain approaching normal. Feed intake by the DM-AE group was also similar to the NC group. The liver and kidney wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
30
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 29 publications
15
30
1
1
Order By: Relevance
“…However, the BG and insulin levels of AEG were similar to those of EEG, suggesting that hypoglycaemic components in VBTL are soluble in both water and alcohol. This observation disagrees with the previous reports in which the hypoglycaemic component was soluble in either water (Kamalakkannan and Prince, 2003;Lee et al, 2008) or alcohol (Vetrichelvan et al, 2002;Arul et al, 2004). The difference may be attributed to there were two kinds of active components responsible for BG lowing activity, which can be soluble in water and alcohol, respectively.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the BG and insulin levels of AEG were similar to those of EEG, suggesting that hypoglycaemic components in VBTL are soluble in both water and alcohol. This observation disagrees with the previous reports in which the hypoglycaemic component was soluble in either water (Kamalakkannan and Prince, 2003;Lee et al, 2008) or alcohol (Vetrichelvan et al, 2002;Arul et al, 2004). The difference may be attributed to there were two kinds of active components responsible for BG lowing activity, which can be soluble in water and alcohol, respectively.…”
Section: Discussioncontrasting
confidence: 99%
“…The body weight loss came accordance with the finding of Oyedemi et al [35]. Lee et al [36] found that the animal treated with STZ appeared ill-looking with the loss of their body weights.…”
Section: Discussionsupporting
confidence: 88%
“…The in-vivo results showed that a daily dose of 200 mg/kg of FPKc inhibited the solid tumor growth and prolonged the survival days of the mice, a group behavior that nearly equaled the one of the CTX group (20 mg/kg/day). A previous study reported that FPK is extensively used in Asia and Europe as a non-toxic anti-diabetes fungus [4]. Additionally, the little alterations of body weight, SI, and TI further confirmed the low in-vitro cytotoxicity of FPKc on normal cells.…”
Section: Discussionsupporting
confidence: 53%
“…Moreover, the fruit bodies are used as anti-inflammatory agents [3]. Additionally, studies report that crude extracellular polysaccharides (EPS) produced in aqueous and alkali extracts of FPK present anti-hyperglycemic activity [4]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation